Prevalence and Determinants of Viral Suppression in Young People Living with HIV on Antiretroviral Therapy in Southern Africa: A Cross-Sectional Analysis of HIV Survey Data of 2020 and 2021. - Msosa, Takondwa Charles; Kabaghe, Alinune; Twabi, Hussein Hassan; Mpinganjira, Samuel; Mzumara, Wongani; Sumari-De Boer, Marion; Aarnoutse, Rob; Wit, Tobias Rinke De; Chipungu, Geoffrey; Ngowi, Kennedy; Kalata, Newton; Mukoka, Madalo; et al. (AIDS & Behavior, 2025)
Young People Living with HIV (YPLHIV, 15–24 years) are an important demographic of Persons Living with HIV (PLHIV) globally and in Southern Africa. However, YPLHIV experience poor outcomes across the HIV diagnostic and treatment cascade due to multiple factors. We estimated the prevalence and determinants of HIV viral suppression in YPLHIV on antiretroviral therapy (ART) in selected Southern African countries. We used publicly available data from Malawi, Zimbabwe, Mozambique, Lesotho, and Eswatini collected during the Population-based HIV Impact Assessments (PHIAs) of 2020 to 2021. Weighted proportions, and 95% confidence intervals (CI) were computed to estimate the prevalence of viral suppression (< 1000c/ml) and bivariate and multivariate analyses were conducted to identify determinants of viral suppression. A total of 855 records of YPLHIV on ART were included in the analysis. The prevalence of viral suppression in YPLHIV on ART was 82.4% (95% CI: 76.7, 86.9). Residing in Mozambique and duration on ART were inversely associated with viral suppression; adjusted odds ratios (AORs) of 0.37 (95% CI: 0.14, 0.95), and 0.87 (95% CI: 0.80, 0.94), respectively. A negative result in the depression screen, being married/cohabitating, and ever switching an ART regimen were positively associated with viral suppression: AORs of 5.78 (95% CI: 2.21, 15.11), 3.72 (95% CI: 1.44, 9.63), and 3.44 (95% CI: 1.69, 7), respectively. YPLHIV had suboptimal viral suppression lower than the UNAIDS 95% targets and may benefit from further research and tailored interventions addressing modifiable factors associated with viral suppression such as depression.